MicroRNA 26a inhibits HMGB1 expression and attenuates cardiac ischemia-reperfusion injury - Li Yao; Xin Lv; Xiaohua Wang (Elsevier, 2016)
Ischemia reperfusion (IR) injury is a major issue in cardiac transplantation and inflammatory processes play a major role in myocardial IR injury. MicroRNA 26a (Mir-26a) plays important roles in cellular differentiation, cell growth, cell apoptosis and metastasis. Mir-26a has been demonstrated to modulate regulatory T cells expansion and attenuates renal IR injury. However, the role of Mir-26a in the cardiac IR injury has never been investigated. In our study, hearts of C57BL/6 mice were flushed and stored in cold Bretschneider solution for 8 hours and then transplanted into syngeneic recipients. The results demonstrate a crucial role for Mir-26a in inhibiting high mobility group box-1 (HMGB1) expression and attenuating cardiac IR injury. Mir-26a overexpression results in attenuated cardiac IR injury and inhibited HMGB1 expression. Mir-26a also inhibits inflammatory cells infiltration and cytokines expression. Furthermore, the attenuated cardiac IR injury induced by Mir-26a was abrogated by additional administration of recombinant HMGB1 (rHMGB1). In conclusion, Mir-26a plays a protective role in cardiomyocyte IR injury and this is associated with inhibited HMGB1 expression.